Workplace violence experienced by nurses in Universiti Kebangsaan Malaysia Medical Centre - Ruth Packiavathy RD; Samsiah M; Hamidah H; Santhna LP (Penerbit UKM, 2009)
Lately, increasing workplace violence is a problem that requires serious attention by the management of the healthcare sector. This study was carried out to examine workplace violence experienced by nurses in the Universiti Kebangsaan Malaysia Medical Centre. It aimed to identify the category of nursing staff who formed the highest number of victims, the perpetrators and the common types of workplace violence. This was a descriptive cross-sectional study carried out over a three month period on 55 nurses who had participated voluntarily in this study. The demographic data and data on the violent incident were collected by using a 21-item questionnaire. The reliability and validity with Cronbach’s alpha was 0.872. Information on the most common types of violence, victims and the perpetrators was also collected. The study revealed that workplace violence among the nursing staff was 3.7% with an average of 1.2% being abused per month and one nurse being abused every other day. The study also revealed that the staff nurses were the most common victims and the perpetrators were mainly the patients (40.6%) and the patients’ relatives (37.5%). The most common forms of violence were verbal abuse (31.9%) and verbal threat (23.7%). Physical violence was experienced by 44.4% of the victims. These results suggest that workplace violence is a serious problem which should be addressed in order to create a safe environment for the nurses.